Dark Web in Narcotics Crime: A Critical Study of Central Jakarta District Court Decision No. 12/Pid.Sus/2023 - Dewi, Dewi; Jayanti, Meivina; Lee, Yonghwa; Putra, Albert Fajar Yuga Yusdi; Bramaditra, Muhammad Elvio (Universitas Muhammadiyah Sumatera Utara, 2025)
The distribution of narcotics through the dark web is a new criminal offense in the Indonesian judicial system. This paper attempts to examine how the court views the use of the dark web as evidence related to criminal cases through an examination of the Central Jakarta District Court Decision No. 12/Pid.Sus/2023. This paper employs a normative legal approach methodology, analyzing each court decision document. The research findings indicate that while electronic evidence demonstrating connections to activities on the dark web has been submitted, there remain significant challenges in proving the connection between such evidence and the elements of the crime. These findings underscore the need for further regulatory improvements alongside enhanced capacity of law enforcement agencies in addressing crimes facilitated by increasingly sophisticated technology today